Abdominal Stiffness Evaluation in Massage for Constipation - Wang, Yunyi (Sensors (Basel), 2021)
According to the experience of nurses and physiotherapists, the abdomen of constipated people becomes softer after abdominal massage. However, the relationship between the decrease in abdominal stiffness and the benefits of abdominal massage has not been examined quantitatively and is unclear. Furthermore, devices for measuring stiffness have been designed to measure relatively hard areas such as the shoulders and do not take into account the lateral outflow of the target tissue, which can be a problem when measuring the stiffness of soft areas such as the abdomen. To address these issues, this study presents a stiffness sensor suitable for measuring abdominal stiffness and investigates the relationship between the reduction in abdominal stiffness and the benefits of abdominal massage. The solution to prevent the lateral outflow of the target is the realization of a stopper, including a contact detection device, which enables a wide-area contact around the targeted area. The sensor consists of a stopper, probe, spring, and time-of-flight (ToF) sensors. The probe and spring provide appropriate pressure and deformation to the abdomen, whereas the stopper prevents the probe from being pushed into the abdomen more than necessary. The ToF sensor measures the deformation length when the deformation is stopped by the stopper. The abdominal stiffness can be derived from the deformation length. The investigation results indicate that the reduction in abdominal stiffness corresponds to the improvement of the stool condition or the maintenance of a healthy stool condition, whereas the maintenance of abdominal stiffness indicates the maintenance or deterioration of the stool condition.